El valor nutricional y el rendimiento académico en la Educación Inicial. Unidad Educativa del Milenio Intercultural Salinas. cantón Guaranda. 2018 - Salazar Guaraca, Diana Paola (2018)
The main objective of the present investigation is to determine the incidence of the nutritional value and the academic performance of the initial education of the Educational Unit of the Intercultural Millenium Salinas, through a nutritional guide oriented to the mothers of family. The mixed methodology was used, which allowed highlighting some qualitative and other quantitative aspects necessary to obtain real results and provide appropriate solutions to mothers for the benefit of their children. In addition, it was determined to carry out research in the Intercultural Education Unit of the Millennium "Salinas" with a population (n = 63 girls and boys), members of Initial 1, Initial 2 and High School and 7 teachers of the area of Initial Education. This study is supported methodologically in the research procedure through the proposal to implement a practical guide that will inform parents about the nutritional value of food improving the academic performance of children who are part of the student population related to the development of the investigation. This can only be achieved with the commitment of everyone involved in this study The guide, implemented and socialized, is of great help since, it allowed the mothers to know about the nutritional values of the food and the importance of them in relation to the academic performance, leaving the possibility to continue a second stage, with the development of a mobile application that meets the same characteristics of orientation towards parents, always marked in the lines of research of the UEB: ICT Management [Software Development], Health and Human Well-being [Children's Health]. Keywords: Junk food, Malnutrition, Obesity, Academic performance, Nutritional value.